Immune thrombocytopaenia at a central hospital in Johannesburg - Mbao, Melvin (My University, 2016)
Background. Primary immune thrombocytopenia (ITP) is a rare disease causing significant morbidity. South Africa has a high prevalence of HIV infection which may be associated with immune thrombocytopenia. There is a paucity of clinical, management and outcome data on immune thrombocytopenia in the local South African setting. Objectives. To compare the demographics, clinical presentation, management and treatment outcomes of immune thrombocytopenia in HIV positive and HIV negative patients and to compare the treatment outcomes with established international guidelines. Methods. This was a retrospective comparative study conducted at Charlotte Maxeke Academic Hospital, Johannesburg, from January 2003 to December 2014. Adults (≥ 18 years) with confirmed diagnosis of ITP were included. Hospital charts of eligible patients were reviewed to extract data on their clinical presentation, diagnosis, HIV status, treatment and outcomes. A comparison was made between HIV positive and negative patients. Descriptive analysis was performed on the data and results were presented graphically. The P-value of <0.05 was regarded as significant. Results. A total of 250 patients were screened, of which 154 patients met eligibility criteria for the study. 91% of the patients were female, 58% were HIV negative and 42% were HIV positive. The 25-35 year age-group comprised the highest percentage of HIV positive patients (42%). There was no difference in the presentation of symptoms between HIV positive and HIV negative patients. Response to first line therapy was not significantly different between the HIV positive and HIV negative patients (p=0.1370). The patients who went on second line therapy, showed excellent response with approximately 80% reaching complete response. There was no difference in HIV positive and HIV negative groups. Conclusion. In a large central hospital in a high HIV prevalence setting, there is no significant difference between HIV positive and HIV negative patients in terms of clinical presentation, treatment and outcomes in confirmed patients with immune thrombocytopenia. The management of ITP at the CMJAH is comparable to that of published guidelines.
A Research Report submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfilment of the degree of Master of Medicine in the branch of Internal Medicine.
Keywords: Purpura, Thrombocytopenic, Idiopathic; HIV Infections